2012
DOI: 10.1002/glia.22366
|View full text |Cite
|
Sign up to set email alerts
|

CD200‐CD200R1 interaction contributes to neuroprotective effects of anandamide on experimentally induced inflammation

Abstract: The endocannabinoid anandamide (AEA) is released by macrophages and microglia on pathological neuroinflammatory conditions such as multiple sclerosis (MS). CD200 is a membrane glycoprotein expressed in neurons that suppresses immune activity via its receptor (CD200R) mainly located in macrophages/microglia. CD200‐CD200R interactions contribute to the brain immune privileged status. In this study, we show that AEA protects neurons from microglia‐induced neurotoxicity via CD200‐CD200R interaction. AEA increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 47 publications
4
102
1
2
Order By: Relevance
“…Hippocampal neuronal cultures were prepared from mice embryos (embryonic day 17-18), as previously described (15). After the dissection, cortices were stripped of meningeal tissue and dissociated in PBS containing trypsin without EDTA (Thermo Fisher Scientific) and deoxyribonuclease I (1 mg/ml; Roche Diagnostics, Manheim, Germany) at 37˚C for 15 min.…”
Section: Murine Neuronal Culturesmentioning
confidence: 99%
“…Hippocampal neuronal cultures were prepared from mice embryos (embryonic day 17-18), as previously described (15). After the dissection, cortices were stripped of meningeal tissue and dissociated in PBS containing trypsin without EDTA (Thermo Fisher Scientific) and deoxyribonuclease I (1 mg/ml; Roche Diagnostics, Manheim, Germany) at 37˚C for 15 min.…”
Section: Murine Neuronal Culturesmentioning
confidence: 99%
“…Prostamides do not show potent interaction with prostanoid receptors, and studies using isolated feline iris cells have suggested the presence of prostamide-sensitive receptors different from the ones responding to PGs (22)(23)(24). The prostamide precursor A-EA has also been shown to exhibit neuroprotective and analgesic roles in infl ammation and pain models ( 25,26 ), Instrument control and data acquisition were performed using the MassLynx™ V4.0 software. For optimization of ESI/MS and ESI/MS/MS conditions, individual standards (10 ng/ l) were introduced into the spectrometer by direct infusion through a syringe pump (fl ow rate 10 l/min) through the HPLC solvent fl ow (rate 0.2 ml/min).…”
Section: Tissue Homogenization and Extraction Of Prostamides And Fattmentioning
confidence: 99%
“…the tissue specifi c distribution of sn -1 docosahexanoyl species of PC ( 43 ). Although A-EA is considered a minor lipid species, representing only 1-10% of total FA-EA in human membranes under basal conditions, studies carried out in brain and nervous tissue indicate A-EA levels are increased in response to injury ( 44,45 ), and that A-EA participates as an antiinfl ammatory agent of the immune response ( 25,46 ). Few studies have examined the actions of A-EA per se in the cornea; however, it is a highly innervated tissue, and CB 1 receptors expressed on corneal sensory nerves stimulated by an agonist were found to support a role in contributing to antinociception in the anterior eye ( 47 ).…”
Section: Analysis Of Napes In Rabbit Corneamentioning
confidence: 99%
“…Theiler's virus (TMEV) induction of inflammatory processes is thought to be primarily mediated via TLR3 activation (So et al, 2006). In vitro data have demonstrated that anandamide downregulates proinflammatory cytokines IL-12, IL-17, TNFα and enhances IL-10 and IL-6 levels in TMEV-infected astrocytes (Molina-Holgado et al, 1997, 1998Correa et al, 2011;Hernangomez et al, 2012). Furthermore, PEA or FAAH inhibition attenuates microglial activation, the expression of pro-inflammatory cytokines and ameliorates motor symptoms in the TMEV-model of multiple sclerosis (Mestre et al, 2005;Ortega-Gutierrez et al, 2005;Loria et al, 2008;Loria et al, 2010;Correa et al, 2011;Hernangomez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%